Factors Associated With Malaria Incidence In Bawootalua Village Lahusa District South Nias Regency In 2019 - Jenni Susi Sihite; Leli Desi Uli Basana Hutagalung (Science Midwifery, 2019)
The API rate in Bawootalua Village, Lahusa District for the last 3 years (2016 - 2018) according to the Lahusa Health Center (Puskesmas Lahusa, 2018) there are still malaria cases. Until now, in Bawootalua Village, Lahusa District, with this condition no research has been conducted on the factors that influence the incidence of Malaria in the area. The study design used was cross sectional with the research population being all residents in Selakambang Village. Samples were taken with a total sampling technique of 138 people. The instrument used in the study was a questionnaire sheet with a relationship analysis using the Chi Square test .